PENGEMBANGAN MEDIA PEMBELAJARAN PPT INTERAKTIF BERBASISPOP UP BOOK DIGITAL PADA PEMBELAJARAN IPS DI KELAS IV SD - Iyai, Yustina; Erita, Yeni (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Abstract—The limited use of innovative instructional media in fourth-grade SocialStudies(IPS) learninghas resulted in teacher-centered instructionand low studentengagement, which affects students' learning outcomes. This study aimed todevelopaninteractivePowerPoint(PPT)learningmediabasedonaDigitalPop UpBookthatisvalid,practical,andeffectiveforfourth-gradeSocialStudieslearninginelementary schools. This research employed a Research and Development (R&D)approach using the ADDIE model, which consists of Analysis, Design,Development, Implementation, and Evaluation stages. Product trials wereconducted at SDN 17 Lubuk Alung and SDN 21 Lubuk Alung, while theimplementation stage was carried out at SDN 01 Lubuk Alung and SDN 20 LubukAlung. The research instruments included expert validation sheets,practicalityquestionnaires for teachers and students, and learning achievement tests tomeasure the effectiveness of the developed media. The findings indicated that theinteractive PPT based on a Digital Pop-Up Book was categorized as very validaccording to the assessments of material, media, and language experts. Thepracticality assessment showed that the media was very practical based onteachers' and students' responses. Furthermore, the effectiveness testdemonstratedasignificantimprovementinstudents'learningoutcomes.Duringtheimplementation stage, the Learning Objectives Achievement Criteria (KKTP)reached 100% at both SDN 01 Lubuk Alung and SDN 20 Lubuk Alung. Therefore,the interactive PPT learning media based on a Digital Pop-Up Book is consideredvalid, practical, and effective, making it suitable for supporting Social Studieslearning in fourth-grade elementary schools.